Are Market Prices for Patent Licenses Observable? Evidence from 4G and 5G Licensing - Love, Brian; Helmers, Christian (Science and Technology Law Review, 2023)
Despite the pervasiveness of patent licensing in many industries, there is a dearth of publicly available information on licensing transactions. Notably, information on price—i.e., the royalty agreed upon by licensor and licensee—is purposefully kept secret. We assess to what extent “market prices” on patent licenses are observable by assembling all publicly available information on royalty amounts associated with the licensing of 4G and 5G standard essential patents (SEPs). Our data come from a range of sources including court verdicts and litigation settlements, arbitration awards, public announcements, and published licensing agreements. We show that even for a highly visible technology such as mobile broadband, the available price points are few and far between. Moreover, any comparison of the available data points, let alone their aggregation, is extremely challenging due to largely unobservable heterogeneity in the terms and scope of the underlying licensing agreements. Our results point to a lack of transparency in the market for patent licensing that might adversely affect market participants and competition more broadly.